Chronological Age and Job Satisfaction: The Young Blue Collar Worker - Altimus, Cyrus A.; Tersine, Richard J. (Academy of Management Journal, 1973)
This study investigated the job satisfaction level of young blue collar workers. The younger workers were found to be significantly lower in satisfaction with work itself, esteem, self-actualization, and total work satisfaction. The perceptions and satisfaction level of young blue collar workers were quite different from their older counterparts.